Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1007/bf00318566
|View full text |Cite
|
Sign up to set email alerts
|

Paired helical filament tau (PHFtau) in Niemann-Pick type C disease is similar to PHFtau in Alzheimer's disease

Abstract: Niemann-Pick Type C disease (NPC) is a cholesterol storage disease with defects in the intracellular trafficking of exogenous cholesterol derived from low density lipoproteins. In NPC cases with a chronic progressive course, neurofibrillary tangles (NFTs) that consist of paired helical filaments (PHFs) have been reported. To determine if NPC tangles contain abnormal tau proteins (known as PHFtau) similar to those found in Alzheimer's disease (AD) tangles, we examined the brains of five NPC cases by immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(83 citation statements)
references
References 19 publications
4
76
0
Order By: Relevance
“…The neurodegenerative disease Niemann-Pick type C is characterized by the buildup of lipoprotein-derived cholesterol in lysosomes due to mutations in the NPC1 protein (Loftus et al 1997). Interestingly, the excessive lysosomal storage of cholesterol may in fact promote abnormal protein processing as evidenced by the appearance of PHF-tau in Niemann-Pick disease resembling that found in AD (Auer et al 1995). This is consistent with reports suggesting that altered tau processing and early PHF formation involve lysosomes of AD brains and model systems (Ikeda et al 1998(Ikeda et al , 2000Oyama et al 1998;Bendiske et al 2002).…”
Section: Alzheimer-type Protein Depositionsupporting
confidence: 87%
“…The neurodegenerative disease Niemann-Pick type C is characterized by the buildup of lipoprotein-derived cholesterol in lysosomes due to mutations in the NPC1 protein (Loftus et al 1997). Interestingly, the excessive lysosomal storage of cholesterol may in fact promote abnormal protein processing as evidenced by the appearance of PHF-tau in Niemann-Pick disease resembling that found in AD (Auer et al 1995). This is consistent with reports suggesting that altered tau processing and early PHF formation involve lysosomes of AD brains and model systems (Ikeda et al 1998(Ikeda et al , 2000Oyama et al 1998;Bendiske et al 2002).…”
Section: Alzheimer-type Protein Depositionsupporting
confidence: 87%
“…2 A striking feature of NPC pathology is the presence in brain of neurofibrillary tangles that, by an array of measures, are indistinguishable from those found in Alzheimer's disease. [3][4][5][6][7] Tangles in the latter case are thought to arise from excessive activation of a set of kinases, including glycogen synthase kinase (GSK-3␤), resulting in the hyperphosphorylation of the microtubule crosslinking protein tau and its assembly into helical filaments. Several in vitro and in vivo studies have implicated GSK-3␤ in tangle formation; 8 -10 moreover, recent work indicates that the kinase co-localizes with intraneuronal tangles and probably accumulates in neurons before the onset of pathology.…”
mentioning
confidence: 99%
“…The latter have greatly facilitated investigation of tau hyperphosphorylation in diseases other than AD. It thus has been shown that lesions made of hyperphosphorylated tau similar to those found in AD are present in Down syndrome (11), Niemann-Pick disease type C (12)(13)(14), Gerstmann-Sträussler-Scheinker (GSS) disease with tangles (15,16), prion protein amyloid angiopathy (17), parkinsonism-dementia complex of Guam (18,19), and familial presenile dementia with tangles (20,21).…”
mentioning
confidence: 99%